Self-gift Giving Consumer Behaviour in Chinese Content - ZHANG, SIQIN (2015)
This research aims to research the motivations, post-purchasing emotions and Chinese culture influence of self-gifting consumer behaviour in Chinese luxury content. To answer the research aim, the qualitative research method is constructed to exploration. Interviews for Chinese different age groups (aged from 20 to 60) are used in this study to get the basic information in the Chinese, which is used for find the motivations, post-purchasing emotions and Chinese culture influence. The differences between the age groups are used to find out if Chinese culture is shifting and whether the shifting of Chinese culture would influence the SGCBs in Chinese luxury market. This research firstly found that young generation (aged 20-30) and the Chinese who are aged from 40 to 50 are more willing to self-gifting them by luxury. Additionally, the most popular reason of self-gifting in luxury is hedonic and the post-purchasing emotions are mostly stable in basic satisfied level. Finally, the Chinese culture seems to be shifting by the globalisation (or modern capitalism) culture which has a different influence in self-gifting behaviours. Those finding are different with the former reviews.